Tugas dan Wewenang Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Rote Ndao dalam Melindungi Anak - Renaldy Zadrian Elimanafe; Saryono Yohanes; Yohanes G. Tuba Helan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The objectives of this research are to understand and analyze the regulation of the duties and authority of the Department of Women's Empowerment and Child Protection in protecting children, and to identify and understand the inhibiting factors in carrying out these duties and authority. The research methodology used is normative juridical research, obtained through interviews and observations, and empirical juridical research, obtained through literature studies. The research results show: (1) The regulation of the duties and authority of the Department of Women's Empowerment and Child Protection in Rote Ndao Regency in protecting children includes the areas of child protection and fulfillment of children's rights and the special child protection program. (2) The inhibiting factors of the Department's duties and authority in protecting children include strategic issues and problems in regional development and strategic issues and problems in the sector of women's empowerment and child protection, population control, and family planning.